The Application of Distillation Technology of Rhizomes Essential Oils in TOGA Community of Sari Hutani in the Border Area of Meru Betiri National Park - Oktavianawati, Ika; Winata, I Nyoman Adi; Aji, Joni Murti Mulyo (Jurnal Inovasi Sains dan Teknologi untuk Masyarakat, 2024)
The TOGA Sari Hutani group has been actively producing traditional herbal medicine using basic ingredients of rhizomes harvested from their gardens. The problem faced by the TOGA group is that the existence of post-harvest rhizomes cannot last well for up to 2-3 months. Meanwhile, the rhizomes used as herbal medicine products have exceeded capacity, especially because consumers and marketing are still limited. According to this, the community service program team from the University of Jember proposed a product diversification from rhizomes in the form of essential oils. This product has a higher selling value and a longer shelf life than traditional herbal medicine products. Essential oil distillation technology has been applied through various activities, such as counselling, distillation practices, mentoring, and monitoring of essential oil production. The Al Kaff essential oil trader, as the second partner in this community service program, is also actively present to provide mentoring regarding essential oil product standards on the market and agreed to become an agent for collecting essential oil products produced by the Sari Hutani group.